Choice of Nanovaccine Delivery Mode Has Profound Impacts on the Intralymph Node Spatiotemporal Distribution and Immunotherapy Efficacy. Issue 19 (15th August 2020) - Wang, Jianghua; Wang, Shuang; Ye, Tong; Li, Feng; Gao, Xiaoyong; Wang, Yan; Ye, Peng; Qing, Shuang; Wang, Changlong; Yue, Hua; Wu, Jie; Wei, Wei; et al.
Abstract: Nanovaccines have attracted booming interests in vaccinology studies, but the profound impacts of their delivery mode on immune response remain unrealized. Herein, immunostimulatory CpG‐modified tumor‐derived nanovesicles (CNVs) are used as a nanovaccine testbed to initially evaluate the impacts of three distinct delivery modes, including mono‐pulse CNVs, staggered‐pulse CNVs, and gel‐confined CNVs. Fundamentally, delivery mode has enormous impacts on the immunomodulatory effects, altering the spatiotemporal distribution of nanovaccine residence and dendritic cell–T cell interaction in lymph nodes, and finally affecting subsequent T cell‐mediated immune performance. As a result, the gel‐confined delivery mode offers the best therapeutic performance in multiple tumor models. When extending evaluation to examine how the various delivery modes impact the performance of liposome‐based nanovaccines, similar trends in intralymph node distribution and antitumor effect are observed. This work provides a strong empirical foundation that nanovaccine researchers should position delivery mode near the top of their considerations for the experimental design, which should speed up nanovaccine development and facilitate efficient selection of appropriate delivery modes in the clinic. Abstract : Nanovaccines constructed with mono‐pulse, staggered‐pulse, or gel‐confined delivery modehave enormous impacts on spatiotemporal distribution and immunoresponse in the lymph nodes. Comparatively, nanovaccines with gel‐confined delivery mode show pronounced lymph node accumulation and dendritic cell–T cell interaction, leading to the best antitumor immunotherapy performance in multiple tumor models. Thus, selection of an appropriate delivery mode should become an integral step for nanovaccine experimental design.